Adverse effects of marijuana use. (2nd April 2016) - Feeney, Kathleen E.; Kampman, Kyle M.
Abstract : Marijuana has consistently been reported as the most commonly used illicit substance in the United States each year. Currently, the legalization of marijuana is up for debate across the nation. While marijuana use is prevalent among the adolescent population, research has shown that there can be devastating effects on health and well-being. A review of the literature shows that marijuana use can have a negative impact on physical health, psychological well-being, and multiple psychosocial outcomes. Adolescents who used marijuana more frequently and began using marijuana at an earlier age experienced worse outcomes and long-lasting effects. Lay Summary: This article reviews recent literature regarding adverse effects of marijuana use. Negative effects of marijuana use relating to physical health, psychological well-being, and outcomes such as academic performance are discussed, especially in relation to the adolescent population .